Bacterial Spectrum and Antimicrobial Susceptibility Patterns in Acquired and Connatal Lacrimal Duct Stenosis. (November 2014) - Prokosch, Verena; Prokosch, Jan-Erik; Promesberger, Julia; Idelevich, Evgeny A.; Böhm, Michael R. R.; Thanos, Solon; Stupp, Tobias
Abstract Purpose: (1) To determine the current bacteriological spectrum in connatal and acquired lacrimal duct obstruction (cLDO and aLDO, respectively) and (2) to analyze the antimicrobial susceptibility patterns of the recovered isolates. Materials and Methods: In a prospective study, 463 samples (30% bilateral LDO) were obtained from the lacrimal ducts of 132 infants and 192 adult patients with symptomatic LDO between 2007 and 2012 at a tertiary eye-care center. The samples were cultured for aerobic and anaerobic bacteria, which were subsequently identified using standard microbiological techniques. Antimicrobial susceptibility testing was performed for each isolate using the disk diffusion method. Data were analyzed using SPSS and chi-square test for significance testing. Results: (1) Among 463 samples investigated, 333 samples were positive, i.e. at least one bacterial isolate was recovered. A total of 72% were recovered (97% of samples from children and 56% of samples from adults), yielding a total of 654 bacterial isolates. Co-colonization with up to five different bacterial species was observed in a large proportion of the samples from children (87%), but in only 20% of those from adults and with a maximum of three different bacteria. Gram-positive bacteria were identified in 72% of the positive samples in both aLDO and cLDO. The most common Gram-positive species in cLDO was Streptococcus pneumoniae (29%), while that in cLDO was Staphylococcus aureus (60%). The most prevalent Gram-negative species were Moraxella catarrhalis (8%) and Haemophilus influenzae (9%) in cLDO and Pseudomonas aeruginosa in aLDO (12%). (2) Susceptibility testing revealed chloramphenicol to be the most active antibiotic with resistance rates of 3% in cLDO and 6% in aLDO, followed by ciprofloxacin (1% and 6%). Erythromycin and gentamicin were the least active of all, with resistances of 41% and 22%, respectively, in cLDO, and 23% and 11% in aLDO. Conclusions: Bacterial colonization occurs regularly in LDO, with Gram-positive bacteria being found in 97% of cLDO samples and 56% of aLDO samples. A remarkable number of different species were found to co-colonize in cLDO. The most common bacteria in LDO are highly susceptible in vitro to chloramphenicol and ciprofloxacin.